Axion Dark Matter Search with Interferometrie Gravitational Wave Detectors. (February 2020) - Nagano, Koji; Obata, Ippei; Fujita, Tomohiro; Michimura, Yuta
Abstract: Axion dark matter differentiates the phase velocities of the circular-polarized photons. In [Phys. Rev. Lett. 123, 111301 (2019)], we have proposed a scheme to measure the phase difference by using a linear optical cavity. If the scheme is applied to the Fabry-Perot arm of Advanced LIGO-like (Cosmic-Explorer-like) gravitational wave detector, the potential sensitivity to the axion-photon coupling constant, g aγ, reaches g aγ ≃ 8 × 10 −13 GeV −1 (4 × 10 −14 GeV −1 ) at the axion mass m ≃ 3 × 10 −13 eV (2 × 10 −15 eV) and remains at around this sensitivity for 3 orders of magnitude in mass. Furthermore, its sensitivity has a sharp peak reaching g aγ ≃ 10 −14 GeV −1 (8 × 10 −17 GeV −1 ) at m = 1.563 × 10 −10 eV (1.563 × 10 −11 eV). This sensitivity can be achieved without loosing any sensitivity to gravitational waves.